Hydrogen-Rich Saline Regulates Microglial Phagocytosis and Restores Behavioral Deficits Following Hypoxia-Ischemia Injury in Neonatal Mice via the Akt Pathway - Ke, Hongfei (Drug Des Devel Ther, 2020)
INTRODUCTION: We have reported previously that hydrogen-rich saline (HS) plays a neuroprotective role in hypoxia-ischemia (HI) brain damage in newborn mice. However, the mechanisms for this neuroprotection resulting from HS remain unknown. In this study, we examined the potential for HS to exert effects upon microglial phagocytosis via involvement of the Akt signaling pathway as one of the neuroprotective mechanisms in response to neonatal HI. METHODS: The HI brain injury model was performed on postnatal day (PND) 7 (modified Vannucci model). The acute brain damage was detected at 3 days after HI exposure. The behavioral and functional screening of the pups at PND11 and PND13 and their long-term outcomes (PND35, 28-days post-HI) were evaluated sensorimotor performance and cognitive functions, respectively. RESULTS: The result showed that HS administration alleviated HI-induced edema, infract volume and cellular apoptosis within the cortex of neonatal mice. Accompanying these indices of neuroprotection from HS were reductions in HI-induced phagocytosis in microglia as demonstrated in vivo and in vitro, effects that were associated with increasing levels of Akt phosphorylation and improvements in neurobehavioral responses. These beneficial effects of HS were abolished in mice treated with an Akt inhibitor. DISCUSSION: These results demonstrate that HS treatment attenuates neurobehavioral deficits and apoptosis resulting from HI, effects which were associated with reductions in phagocytosis and appear to involve the Akt signaling pathway.